2017
DOI: 10.1007/s00423-016-1538-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a preoperative immune-modulating diet in patients with esophageal cancer: a prospective parallel group randomized study

Abstract: Preoperative IMD suppressed the elevation of the TNF-α levels after thoracoscopic esophagectomy in patients with esophageal cancer, although no different tendency was detected in terms of IL-6, CRP or postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…Moon et al 32 showed that oleic acid and linolenic acid could downregulate the malignant potential of OE19 and OE33 esophageal cancer cells, mainly through regulating the AMPK/S6 axis. Kitagawa et al 33 found that γ-linolenic acid inhibited esophageal tumor growth based on clinical statistical data. The antitumor activities of lactoferrin or the three unsaturated fatty acids alone have been widely validated, but the effect of lactoferrin + oleic acid/DHA/linolenic combinations in inhibiting esophageal tumors has been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Moon et al 32 showed that oleic acid and linolenic acid could downregulate the malignant potential of OE19 and OE33 esophageal cancer cells, mainly through regulating the AMPK/S6 axis. Kitagawa et al 33 found that γ-linolenic acid inhibited esophageal tumor growth based on clinical statistical data. The antitumor activities of lactoferrin or the three unsaturated fatty acids alone have been widely validated, but the effect of lactoferrin + oleic acid/DHA/linolenic combinations in inhibiting esophageal tumors has been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Among 14 eligible studies, nine (13, 14, 37, 38, 40-42, 45, 46) reported the details of generating random sequence such as computerized random program and random number table. Eight studies (13,14,37,(39)(40)(41)(42)(43) correctly performed allocation concealment, and three studies (13,14,42) did not blind participant, personnel or outcome assessor. Details of the risk of bias were summarized in Fig.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Previous studies suggested that enteral nutrition (EN) can effectively decrease the risk of postoperative complications and enhance the recovery among patients undergoing gastrointestinal surgery compared to parenteral nutrition (PN) (9)(10)(11). However, standard EN do not contain immuneenhancing ingredients of improving host immunity and relieving in ammatory response (12), and thus additional immune-modulating substances such as arginine and omega-3 polyunsaturated fatty acids has been added to standard EN, which is de ned as enteral immunonutrition (EIN) (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, that trial showed a significant difference in the 6-month survival rates between the intervention group and the control group (92 vs. 72%; p = 0.028). One prospective randomized trial by Kitagawa et al [27] evaluated the effects of preoperative IN in patients undergoing thoracoscopic esophagectomy. In that study, MHN-02 (MEIN ® ; Meiji Dairies Co., Tokyo, Japan) as an immune-modulating diet was administrated during the 5 days before surgery.…”
Section: In In Patients Undergoing Esophagectomymentioning
confidence: 99%
“…Four trials [21,23,25,27] compared the preoperative administration of IN with an ordinary diet. Three trials were retrospective studies and one was a prospective randomized study.…”
Section: In In Patients Undergoing Esophagectomymentioning
confidence: 99%